Gender wage gap in departament of Santander, Colombia (2016)
This paper analyzes the factors that influence hourly wage and their differencesby gender, for the Department of Santander, Colombia, during theyears 2012 to 2014. Specifically, it explores whether the differential is dueor not to a discriminatory factor in labor market of Santander, using datafrom Colombian household survey “Gran Encuesta Integrada de HogaresGEIH”. After the descriptive analysis of the labor market in Santander, wemake econometric estimations using the Blinder Oaxaca methodology toprove the existence of a discriminatory component. Results indicate that,for the total sample in the Santander region, between 25 % and 30 % of thewage differentials by gender are associated to the unexplained discriminatorycomponent.